2013
DOI: 10.1177/1947601913499020
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Mediated Transfer of a Novel Long Noncoding RNA TUC339: A Mechanism of Intercellular Signaling in Human Hepatocellular Cancer

Abstract: Although the expression of long noncoding RNA (lncRNA) is altered in hepatocellular cancer (HCC), their biological effects are poorly defined. We have identified lncRNA with highly conserved sequences, ultraconserved lncRNA (ucRNA) that are transcribed and altered in expression in HCC. Extracellular vesicles, such as exosomes and microvesicles, are released from tumor cells and can transfer biologically active proteins and RNA across cells. We sought to identify the role of vesicle-mediated transfer of ucRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
247
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(255 citation statements)
references
References 23 publications
7
247
0
1
Order By: Relevance
“…We recently reported that extracellular vesicles derived from malignant hepatocytes contain microRNAs that can be transferred to other recipient cells and, moreover, can modulate cell signaling and cell viability in these recipient cells (Kogure et al, 2011). We have also identified lncRNAs, such as TUC339, that can be selectively enriched within these vesicles (Kogure et al, 2013). These observations support the presence of highly selective mechanisms for incorporating ncRNA into extracellular vesicles and support a role for ncRNAs as effectors of intercellular signaling (Valadi et al, 2007;Saunderson et al, 2008;Skog et al, 2008).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We recently reported that extracellular vesicles derived from malignant hepatocytes contain microRNAs that can be transferred to other recipient cells and, moreover, can modulate cell signaling and cell viability in these recipient cells (Kogure et al, 2011). We have also identified lncRNAs, such as TUC339, that can be selectively enriched within these vesicles (Kogure et al, 2013). These observations support the presence of highly selective mechanisms for incorporating ncRNA into extracellular vesicles and support a role for ncRNAs as effectors of intercellular signaling (Valadi et al, 2007;Saunderson et al, 2008;Skog et al, 2008).…”
Section: Introductionsupporting
confidence: 65%
“…Human HCC cell lines HepG2, Hep3B, PLC-PRF5 and Huh-7 were obtained from the American Type Culture Collection (Manassas, VA), and HepG2.ST was derived from HepG2 cells by spontaneous transformation (Kogure et al, 2013). Cells were cultured in Dulbecco's modified Eagle's high-glucose medium (HyClone, Logan, UT), containing 10% fetal bovine serum (FBS) and 1% antibiotic-antimycotic (Life Technologies, Grand Island, NY), at 37˚C under 5% CO 2 .…”
Section: Cell Lines Culture and Reagentsmentioning
confidence: 99%
“…Subsets of mRNAs, miRNAs, and long noncoding RNAs can be transferred through EVs to recipient cells, inducing functional and phenotypic changes. 130,131 In particular, the horizontal transfer of miRNAs has been proposed as a new form of intercellular communication, representing a means by which donor cells can regulate the gene expression of recipient cells. 132 EVs extend the trophic repertoire of MSCs from the classical secreted growth factors to now include as well mRNAs, miRNAs, lipids, and membrane bound proteins.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Kogure et al [55] first demonstrated that lncRNA with highly conserved sequences ultraconserved RNAs (ucRNAs) influences intercellular signalling. In HCC cell lines PLC/PRF/5 and Hep3B, the intercellular transfer of ucRNA TUC339 by exosomes represents a unique signalling mechanism by which tumour cells can promote HCC growth and spread [55] . Thus, the use of exosomes as biological delivery vehicles is of considerable interest.…”
Section: Intercellular Communicationmentioning
confidence: 99%